Deflective Whiteness Co-Opting Black and Latinx Identity Politics - Noel, Hannah (The Ohio State University Press, 2022)
Details the appropriation of social justice rhetoric to claim Whiteness as an aggrieved social status, enabling White supremacy and deepening racial inequities.